Case study of safety management practices at Daibochi Plastics Sdn Bhd - Abdul Ghafar, Mohd Firdaus (2011)
Safety management is commonly understood as applying a set of principles, framework, processes and measures to prevent accidents, injuries and other adverse consequences that may be caused by using a service or a product. It is that function which exists to assist managers in better discharging their responsibilities for operational system design and implementation through either the prediction of system’s deficiencies before errors occur or the identification and correction of system’s deficiencies by professional analysis of safety occurrences. The objective of safety management in the packaging industry is to prevent human injury or loss of life, and to avoid damage to the environment and to property. (John Illson, Integrated Safety Mangement Section). Safety comes at a price. All organizations have limited resources to devote to safety, and must deal continually with the conflicting goals of safety versus productivity, efficiency, or customer service objectives, which ultimately determine profitability. This study is attempted to discover how Daibochi Plastics take an actions to resolve this circumstance base on the type of safety management that they take as a guidelines to resolve the problem. At the same time this study will explain details about type of safety management and how to prevent it well. In addiction it will help the company recognize all this elements as a key success to prevent hazards and teach their employee about knowledge of safety in workplace.